Mechanical properties of concrete at early ages. - Zhao, Jianwei. (University of Ottawa (Canada), 1990)
Modern construction techniques enable reinforced concrete structures to be constructed in a very short time. The loads occurring due to the construction process on the partially completed structure can be larger than the design service load. The available strength of the immature partially completed structure is dependent upon the available concrete strength which may be less than the specified strength. Failure would occur if the available strength is less than that required to support the construction loads. The construction loads can also cause significant immediate deflection due to concrete cracking and its low early age modulus of elasticity. Because of the high applied stress/developed strength ratio and shrinkage, the time dependent deflection may be unacceptably large. This thesis examines the early age behaviors of concrete tensile strength, modulus of elasticity, concrete shrinkage and creep, and develops prediction equations which are demonstrated to be more appropriate than the current code equations.
Keywords: Engineering, Civil.